Highly selective dissolution and synchronous extraction of zinc from zinc-cobalt slag by an ionic liquid [Hbet][Tf2N]–H2O system: A novel method for separating zinc and cobalt. (15th September 2021) - Huang, Yukun; Duan, Zhuo; Bai, Ningning; Wang, Huijuan; Cao, Yijun; Song, Xiangyu; Peng, Weijun; Zhu, Xiaofeng
Abstract: Zinc-cobalt slag produced from zinc hydrometallurgical process is a hazardous solid waste containing heavy metal ions; it is a secondary source of cobalt. Separating zinc and cobalt is the key problem in the comprehensive recovery. Here, a novel clean method for separating zinc and cobalt using a carboxyl-functionalized ionic liquid, ([Hbet][Tf2 N]), is proposed. This innovative method provides a dual separation mode with selective dissolution and extraction during the heating and cooling of the [Hbet][Tf2 N]–H2 O system, and a higher separation effect on zinc and cobalt is obtained. The dissolution ratio of zinc oxide is 92.6% at 90 °C and 60 min, whereas the dissolution of cobalt and manganese is negligible (5.37% and 0.05%, respectively). The selective dissolution of metal oxide M x O y in [Hbet][Tf2 N]–H2 O is explained using a U/x value that correlates with the lattice energy, U, of metal oxide. In addition, the recovery of Zn and regeneration of the ionic liquid is implemented by back extraction of Zn-loaded [Hbet][Tf2 N] using an oxalic acid solution. This study presents an efficient method for separating of zinc and cobalt using a dual-mode selective dissolution and synchronous extraction, which is a promising technique for separating similar metallic elements. Graphical abstract: Based on the stratification characteristics of [Hbet][Tf2 N] and aqueous solution, the efficient separation of zinc and cobalt is achieved by the selective dissolution and synchronous extraction of zinc from zinc-cobalt slag by the [Hbet][Tf2 N]-H2 O system in the heating and cooling process. The recovery of zinc and regeneration of [Hbet][Tf2 N] were realized by the back-extraction of Zn-loaded [Hbet][Tf2 N] with oxalic acid solution. Image 1 Highlights: A new clean system of separating zinc and cobalt was proposed by using ionic liquid. Separation of Zinc and Cobalt was obtained by selective dissolution and extraction. Recovery of zinc and regeneration of ionic liquid were realized by back-extraction.